Portrait Analysis of Early Childhood Education in Cities and Villages: The COVID-19 Pandemic Era - Masruroh, Lely; Munastiwi, Erni (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
Abstract: The COVID-19 pandemic has affected significant aspects of our society. In addition to degrading the economic system and human health throughout the world, it disrupts educational activities running in general. With the government's policy of having to stay home, education is diversion through online learning. Online learning is applied to school institutions throughout Indonesia, both in the village and in the city. Network access and facilities in urban areas are better than in rural areas. This research is essential to be conducted as input to equalize online learning support facilities in the ponorogo area of east Java. The method in this study uses qualitative with library studies and at the same time research in the field. Data retrieval using interview and journal analysis techniques after related books. The results of the study suggest that online learning conducted in the city tends to be more effective because of the ease of easy-to-diakse facilities and the full support of parents. Meanwhile, in the village online learning is less effective due to the lack of adequate facilities and lack of support from parents.Analisis Potret Pendidikan Anak Usia Dini di Kota dan Desa: Era Pandemi COVID-19Abstrak: Pandemi COVID-19 telah mempengaruhi aspek-aspek penting dari masyarakat kita. Selain merusak sistem ekonomi dan kesehatan manusia di seluruh dunia, mengganggu kegiatan pendidikan yang berjalan secara umum. Dengan adanya kebijakan pemerintah untuk tetap di rumah, pendidikan menjadi pengalihan melalui pembelajaran online. Pembelajaran online diterapkan pada institusi sekolah di seluruh Indonesia, baik di desa maupun di kota. Akses jaringan dan fasilitas di perkotaan lebih baik daripada di pedesaan. Penelitian ini penting dilakukan sebagai masukan untuk pemerataan fasilitas penunjang pembelajaran online di wilayah ponorogo Jawa Timur. Metode dalam penelitian ini menggunakan kualitatif dengan studi kepustakaan dan sekaligus penelitian di lapangan. Pengambilan data menggunakan teknik wawancara dan analisis jurnal setelah buku terkait. Hasil penelitian menunjukkan bahwa pembelajaran online yang dilakukan di kota cenderung lebih efektif karena kemudahan fasilitas yang mudah diakse dan dukungan penuh dari orang tua. Sedangkan di desa pembelajaran online kurang efektif karena fasilitas yang kurang memadai dan kurangnya dukungan dari orang tua.